Impact Of Doping And Additive Applications On Photocatalyst Textural Properties In Removing Organic Pollutants: A Review - Safia Syazana Mohtar; Farhana Aziz; Ahmad Fauzi Ismail; Nonni Soraya Sambudi; Hamidah Abdullah; Bunsho Ohtani; Ahmad Nazrul Rosli (Multidisciplinary Digital Publishing Institute (MDPI), 2024)
Indexed by WOS/Scopus/ERA